Effects of Bisphosphonates on Bone Fracture Healing: An Overview on New Preclinical Animal and Clinical Studies - Alidadi, Soodeh; Oryan, Ahmad (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This review covers the bisphosphonates (BPs) characteristics as a treatment choice for osteoporosis and their discrepancies as per  available literature. In addition, the current study reviewed the effects of these antiresorptive compounds on bone fracture healing in  experimental animal model studies. BPs have been commonly used in treating various skeletal diseases such as Paget’s disease and  osteoporosis. BPs reduce bone regeneration or resorption by inhibiting the osteoclast activities and thus, maintain or enhance bone  mineral density when administered to osteoporotic patients. Given the critical importance of bone resorption during the bone healing  process, the use of this class of medications is doubtful and controversial. Although some studies confirmed the efficient application  of BPs, concerns about the possibility of delayed or impaired bone healing, non-union, or mal-union after BP administration have been  raised in some other studies. Moreover, long-term BP administration like zoledronate is associated with some side effects such as atypical  femoral fracture and osteonecrosis of the jaw. As a result, it can be accomplished that dose, timing, and duration of BP administration  are important factors that establish the efficacy of BPs on the healing of different types of bone defects such as tooth extraction, spinal  fusion, calvarial bone, and long bones. Further studies are needed for finding more safe and efficient substitutes for BPs to minimize  or eliminate their undesirable effects.
Keywords: Bisphosphonate; Bone healing; Fracture; Osteonecrosis; Osteoporosis